Keparalelan Fisika Modern dengan Nilai-Nilai Tasawuf - Saparwadi, Saparwadi; Akhmad Sahrandi (Al-Jadwa: Jurnal Studi Islam, 2022)
The world of physics for scientists is no longer a materialist empirical world, but leads to efforts to realize spirituality through science to find the highest essence of science. There is a parallel in thought between Sufism and modern physics, where Sufism is based on direct understanding into the natural world of reality and modern physics is based on on observations of natural phenomena and scientific experiments which are interpreted and communicated through words which will become too abstract when close to reality which causes awareness of facts. Sufism has very many values in modern physics, but this may be unnoticed by the Muslim community. Whereas in Sufism which takes the verses of the Qur'an there are many things that are actually in modern physics quantized in the form of formulas, which we can take as the rationality of the highest existence of the Creator (Allah Subhaanahu Wa Ta'ala). so that modern physics can be used as an analysis of the verses of the Qur'an in demonstrating the essence of spirituality. This study uses the Library Research method with the main data source from the library in the form of books, articles, encyclopedias, dictionaries, and other written sources. To collect data through several stages, namely data inventory through collection of scientific works. The results of the research show that there are parallels between the thoughts in Sufism and modern physics regarding matter in this universe.